D-dimer, CRP, PCT, and IL-6 Levels at Admission to ICU Can Predict In-Hospital Mortality in Patients with COVID-19 Pneumonia. (28th February 2022) - Milenkovic, Marija; Hadzibegovic, Adi; Kovac, Mirjana; Jovanovic, Bojan; Stanisavljevic, Jovana; Djikic, Marina; Sijan, Djuro; Ladjevic, Nebojsa; Palibrk, Ivan; Djukanovic, Marija; Velickovic, Jelena; Ratkovic, Sanja; et al.
Abstract : Introduction . Health care workers have had a challenging task since the COVID-19 outbreak. Prompt and effective predictors of clinical outcomes are crucial to recognize potentially critically ill patients and improve the management of COVID-19 patients. The aim of this study was to identify potential predictors of clinical outcomes in critically ill COVID-19 patients. Methods . The study was designed as a retrospective cohort study, which included 318 patients treated from June 2020 to January 2021 in the Intensive Care Unit (ICU) of the Clinical Hospital Center "Bezanijska Kosa" in Belgrade, Serbia. The verified diagnosis of COVID-19 disease, patients over 18 years of age, and the hospitalization in ICU were the criteria for inclusion in the study. The optimal cutoff value of D-dimer, CRP, IL-6, and PCT for predicting hospital mortality was determined using the ROC curve, while the Kaplan-Meier method and log-rank test were used to assess survival. Results . The study included 318 patients: 219 (68.9%) were male and 99 (31.1%) female. The median age of patients was 69 (60-77) years. During the treatment, 195 (61.3%) patients died, thereof 130 male (66.7%) and 65 female (33.3%). 123 (38.7%) patients were discharged from hospital treatment. The cutoff value of IL-6 for in-hospital death prediction was 74.98 pg/mL (Sn 69.7%, Sp 62.7%); cutoff value of CRP was 81 mg/L (Sn 60.7%, Sp 60%); cutoff value of procalcitonin was 0.56 ng/mL (Sn 81.1%, Sp 76%); and cutoff value of D-dimer was 760 ng/mL FEU (Sn 63.4%, Sp 57.1%). IL-6 ≥ 74.98  pg/mL, CRP ≥ 81  mg/L, PCT ≥ 0.56  ng/mL, and D-dimer ≥ 760  ng/mL were statistically significant predictors of in-hospital mortality. Conclusion . IL-6 ≥ 74.98  pg/mL, CRP   values ≥ 81  mg/L, procalcitonin ≥ 0.56  ng/mL, and D-dimer ≥ 760  ng/mL could effectively predict in-hospital mortality in COVID-19 patients.